The Effect Of Knowledge Creation On The Competitiveness Of Msmes In The Sigerhub Business Incubator Bandar Lampung Through Innovation As A Mediating Variable - Abid Hanan Rianda; Ayi Ahadiat (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of Knowledge Creation on the competitiveness of MSMEs participating in the SigerHub Business Incubator in Bandar Lampung and to examine the mediating role of innovation. The research employs an associative quantitative approach, with primary data collected through questionnaires administered to 130 MSME owners/managers under SigerHub’s incubation. Validity was tested using factor loading (>0.7) and AVE (>0.5), while reliability was measured using Cronbach’s Alpha (>0.7). Data were analyzed using SmartPLS SEM (Structural Equation Modeling), and hypothesis testing was conducted through bootstrapping. The results show that Knowledge Creation has a positive and significant effect on MSME competitiveness, and Innovation positively and significantly mediates the relationship between Knowledge Creation and Competitiveness. These findings indicate that knowledge creation through socialization, externalization, combination, and internalization can accelerate product/process innovation, thereby enhancing MSME profitability and productivity. Practically, MSMEs are encouraged to strengthen knowledge creation processes through training, knowledge-based SOPs, and collaboration. SigerHub is advised to enhance innovation development programs, while the government is expected to expand technological and financial support.